T-Cell–Derived miRNA-214 Mediates Perivascular Fibrosis in Hypertension. Issue 8 (10th April 2020) - Nosalski, Ryszard; Siedlinski, Mateusz; Denby, Laura; McGinnigle, Eilidh; Nowak, Michal; Cat, Aurelie Nguyen Dinh; Medina-Ruiz, Laura; Cantini, Marco; Skiba, Dominik; Wilk, Grzegorz; Osmenda, Grzegorz; Rodor, Julie; et al.
Abstract : Rationale: Despite increasing understanding of the prognostic importance of vascular stiffening linked to perivascular fibrosis in hypertension, the molecular and cellular regulation of this process is poorly understood. Objectives: To study the functional role of microRNA-214 (miR-214) in the induction of perivascular fibrosis and endothelial dysfunction driving vascular stiffening. Methods and Results: Out of 381 miRs screened in the perivascular tissues in response to Ang II (angiotensin II)-mediated hypertension, miR-214 showed the highest induction (8-fold, P =0.0001). MiR-214 induction was pronounced in perivascular and circulating T cells, but not in perivascular adipose tissue adipocytes. Global deletion of miR-214 − /− prevented Ang II-induced periaortic fibrosis, Col1a1, Col3a1, Col5a1, and Tgfb1 expression, hydroxyproline accumulation, and vascular stiffening, without difference in blood pressure. Mechanistic studies revealed that miR-214 −/− mice were protected against endothelial dysfunction, oxidative stress, and increased Nox2, all of which were induced by Ang II in WT mice. Ang II-induced recruitment of T cells into perivascular adipose tissue was abolished in miR-214 −/− mice. Adoptive transfer of miR-214 −/− T cells into RAG1 −/− mice resulted in reduced perivascular fibrosis compared with the effect of WT T cells. Ang II induced hypertension caused significant change in the expression of 1380 T cell genes in WT, but only 51 in miR-214 −/− . T cell activation, proliferation and chemotaxis pathways were differentially affected. MiR-214 −/− prevented Ang II-induction of profibrotic T cell cytokines ( IL-17, TNF-α, IL-9, and IFN-γ ) and chemokine receptors (CCR1, CCR2, CCR4, CCR5, CCR6, and CXCR3). This manifested in reduced in vitro and in vivo T cell chemotaxis resulting in attenuation of profibrotic perivascular inflammation. Translationally, we show that miR-214 is increased in plasma of patients with hypertension and is directly correlated to pulse wave velocity as a measure of vascular stiffness. Conclusions: T-cell–derived miR-214 controls pathological perivascular fibrosis in hypertension mediated by T cell recruitment and local profibrotic cytokine release. Abstract : Supplemental Digital Content is available in the text.